Lateral dislocation with occurrence of buccal bone plate fracture in a deciduous tooth: clinical case study - Maria Luiza da Matta Felisberto Fernandes; Suzana Coulaud da Costa Cruz; Barbara Teles Terzis Loureiro (Faculdade São Leopoldo Mandic, 2024)
ABSTRACT Dental trauma can happen at any stage of life; however, it is very common in preschool and school aged children. Dislocation injuries in the primary dentition are the most commonly described traumatic dental injuries in the literature. Tooth displacement in the primary dentition is favored due to the greater porosity and resilience of the alveolar bone. Through the study of a clinical case, this article presents the clinical conduct performed in the case of trauma of lateral dislocation with involvement of a fracture of the buccal bone plate in order to assist the clinical practice of dentists who care for children. The treatment carried out in this clinical case study took into account the magnitude of the displacement, the degree of development of the tooth and its relationship with the permanent germ, the length of time since the trauma, and the degree of cooperation of the child in the face of the suggested treatment. This treatment does not only involve emergency intervention; the patient must undergo a radiographic clinical follow-up and control after 30, 60 and 120 days, as well as annually, until the Exfoliation of the deciduous tooth. The child's health was restored aesthetically and functionally.